Effect of the supplementation of exogenous complex non-starch polysaccharidases on the growth performance, rumen fermentation and microflora of fattening sheep - Xue, Yuyang; Sun, Haobin; Guo, Hongyong; Nie, Cunxi; Nan, Shanshan; Lu, Qicheng; Chen, Cheng; Zhang, Wenju (Frontiers in Veterinary Science, 2024)
The objective of this study was to evaluate the effects of exogenous non-starch polysaccharidases (a mixture of cellulase, xylanase, β-glucanase and mannanase) on the growth performance and nutrient digestibility, rumen fermentation, and rumen microflora of sheep. The animal trial was conducted using 36 5-month-old female fattening hybrid sheep (Duolang♂ × Hu♀) who were randomly assigned into four groups comprising nine sheep per treatment: CON, T1, T2, and T3, with 0, 0.1, 0.3, and 0.5% NSPases/kg DM of TMR, respectively. This complex enzyme product was screened for optimal ratios based on previous in vitro tests and responded positively to the in vitro fermentation of the TMR. When treated with NSPases, there was a non-linear effect of average daily gain and feed conversion rate, with the greatest improvement observed in the T2 group. There were no significant differences (p > 0.05) in nutrient intake or apparent digestibility among the NSPase-supplemented groups. In addition, T2 group had a significantly higher acetate to propionate ratio and pH (p < 0.05) than the other groups, and NH3-N and microbial protein concentrations showed a quadratic curve. The results revealed that both immunoglobulins and serum hormones increased linearly with addition (p < 0.05). As the T2 group showed the best growth performance, the CON and T2 groups were subjected to rumen metagenomic analysis. The results showed higher abundance of bacteria and lower abundance of Viruses in the rumen microbiota of the T2 group compared to the CON group. In addition, Uroviricota and Proteobacteria abundance was significantly lower in the T2 group than in the CON group at the phylum level (p < 0.05). These results suggest that the supplementation of high-concentrate rations with NSPases enhance immunity, reduces virus abundance in the rumen, improves rumen health, and promotes rumen fermentation. Our findings provide novel insights for improving growth performance and alleviating inflammatory responses arising from high concentrate feeding patterns in ruminants. However, the biological mechanisms cannot be elucidated by exploring the composition of rumen microbe alone, and further studies are required.